Real communication : how to be you and lead true - Dolan, Gabrielle (John Wiley & Sons Australia, 2019)
Recent changes in big business has seen the expectations of employees evolve and the now demand a new style of communication from their leaders. We have seen unprecedented disruption through organisational change, levels of trust have plummeted, the collision of multigenerational workforces and with the rise and rise of technology baffling phrases and acronyms have proliferated. People have never felt so isolated and confused. This book reveals how to guide and communicate in a way that is authentic and will help to truly connect and engage with people including teams, customers, co-workers.